(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
The reaction of tetrathiazyldihydridofluoride (S4N4H2F2) with Cd(II) Chloride was carried out in organic medium the product obtained was characterized on the basis of IR, UV, EPR, Mass and 1H NMR Spectra and is formulated as (S3N4H2F2CdCl)x where x=2.32